THE ROLE OF BHAYANGKARA AS THE TRUSTEE OF COMMUNITY SECURITY AND ORDER IN SETTLEMENT OF CRIMINAL ACTS OF DOMESTIC VIOLENCE THROUGH PENAL MEDIATION - Denis Restyana (Journal Philosophy of Law, 2020)
Bhabinkamtibmas has the function of carrying out consultation, mediation, negotiation, facilitation, motivation to the community in Harkamtibmas, and solving crime and social problems. With the task as intended, this study will try to examine and analyze how the role of Bhabinkamtibmas in criminal acts of domestic violence (KDRT) through penal mediation at the Weleri Police, Kendal Resort Police and how the obstacles faced in resolving criminal acts of domestic violence (KDRT) through penal mediation by Bhabinkamtibmas at the Weleri Police, Kendal Resort Police. This study uses a sociological juridical approach, which means that this research is examined by looking at the findings of facts in the field, which are used as the basis of the author as data obtained from the field (non-doctrinal) with the existing reality. Based on the results of the study, data obtained that (1) the role of Bhabinkamtibmas in resolving criminal acts of domestic violence (KDRT) through Penal Mediation at the Weleri Police, Kendal Police, aims to obtain more effective and efficient results in controlling crime by maximizing the role of law enforcement officers, in this case, the police in resolving cases through penal mediation. First, the police as a facilitator for both parties. Second, the police also often play a role as mediators in penal mediation and build joint participation between perpetrators, victims, and the community in resolving an event or crime. The problems faced can be appropriately resolved by ensuring a sense of justice, especially for victims. (2) The obstacles faced in settlement of criminal acts of domestic violence (KDRT) through penal mediation by Bhabinkamtibmas at the Weleri Police, Kendal Police are: (1) Not familiar with the settlement process through mediation; (2) The existence of a third party who interferes in solving a problem; (3) The legal basis is not yet strong in resolving through mediation; (4) The Criminal Justice System spearheads the investigation process; (5) The parties do not comply with the mediation decision; (6) Public distrust of law enforcement officers (Bhabinkamtibmas) becomes a mediator.